The Retos journal is in the second quartile of Scopus: a bibliometric analysis from 2016 to 2023 - Muhammad Eka Mardyansyah Simbolon (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The Journal of Retos has been selected to be included in Scopus' second quartile in the fields of education, orthopaedics and sports medicine, physiotherapy, sports therapy, and rehabilitation starting from January 25, 2024. Although it is worth mentioning that this accomplishment came almost ten years after the magazine Retos was included in Scopus in 2016, it has now risen to the second quartile. The objective of the study is to present a graphical representation of the scientific patterns observed in the journal Retos from 2016 to 2023. Bibliometric analysis facilitates the identification and examination of scientific trends, as well as the assessment of research structure, patterns, and trends. Hence, bibliometric analysis is a pertinent and crucial approach for attaining the goals of this study. We conducted an analysis on a dataset consisting of 2334 entries obtained from the Scopus data center. This study employed the software VOSviewer and Rstudio for doing bibliometric analysis. The findings suggest that the topics of physical education and physical activity are prevailing. The growing specialized topics are BAPNE techniques and neuromotricity. Journal Retos has made significant contributions to the advancement of knowledge in various areas, including education, orthopaedics, sports medicine, physiotherapy, sports therapy, and rehabilitation, on a global scale.